Stress to the Bone around Orthodontic Implants in the Mandibular Molar Region: A Finite Element Evaluation - Rogério Coelho de Aguiar (Stomatos, 2012)
Mini-screw implants have been commonly used for orthodontic anchorage. However, the behavior of implants may vary according to their location, inclination, loading position and loading direction. The objective of this study was to apply fi nite element to analyze stress distribution around mini-implants inserted into the buccal cortical bone, in the inferior molar region, when a force of 3 N was applied, varying implant inclination and loading direction, also simulating immediate loading and osseointegration conditions. We carried out a threedimensional analysis of a human cadaveric mandible and of a 9 mm length, 1.5 mm diameter titanium implant. The implant model was introduced into the buccal cortical bone, between the fi rst and second mandibular molars. Finite-element analysis of the implant-bone structure was carried out applying a constant force of 3 N at varying angles (15, 30, 45, 60, 75, and 90 degrees), and in fi ve different positions along the bone surface axis (perpendicularly, vertically at ± 10 degrees, and horizontally at ± 20 degrees). Out of all combinations tested, stress affected only the cortical bone, not being intense enough to cause cortical bone resorption. Stress distribution varied slightly (8.55 to 38.74 Mpa) due to implant inclination and loading direction. Immediate loading generated greater tensions (12.70 to 38.74 Mpa) when compared to osseointegration (8.55 to 21.44 Mpa). A force of 3 N did not result in a tension that could cause cortical bone resorption. Immediate loading resulted in greater tensions to the bone, regardless of implant inclination and loading direction.